2017
DOI: 10.1155/2017/4271483
|View full text |Cite
|
Sign up to set email alerts
|

Using Novel Technology within a School-Based Setting to Increase Physical Activity: A Pilot Study in School-Age Children from a Low-Income, Urban Community

Abstract: Background Less than half of American children meet national physical activity (PA) recommendations. This study tested the feasibility, acceptability, and preliminary effectiveness of using wearable PA monitors to increase PA in school-age children. Methods In Phase 1 of this study, conducted in 2014, 32 fifth-grade students enrolled in a low-resource middle school were given a waist-worn Fitbit Zip monitor for 4 weeks to test its feasibility (adherence) and acceptability. Adherence, wear time of ≥8 hours per … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 33 publications
3
41
0
Order By: Relevance
“…The findings from this study support previous research that shows that wearable technology interventions are both acceptable among adolescents [ 11 ] and feasible for implementation within the school setting [ 10 ]. Overall, there were few sex differences in adolescent males’ and females’ experiences and perceptions of RAW-PA, apart from males being significantly more likely than females to like the Facebook page and weekly videos.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The findings from this study support previous research that shows that wearable technology interventions are both acceptable among adolescents [ 11 ] and feasible for implementation within the school setting [ 10 ]. Overall, there were few sex differences in adolescent males’ and females’ experiences and perceptions of RAW-PA, apart from males being significantly more likely than females to like the Facebook page and weekly videos.…”
Section: Discussionsupporting
confidence: 88%
“…There is a dearth of data about wearable activity tracker ownership in adolescents, although one study found that approximately 25% of adolescents owned such devices, with more males than females reporting ownership [ 9 ]. Of note, school-based research has shown that wearable activity monitors have moderate acceptability among school-aged children in low-income communities [ 10 ]. Furthermore, there is some initial evidence that adolescents are generally positive about the use of wearable technology for tracking physical activity, and use device features to set goals and undertake challenges against friends [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fitbit brand trackers have been largely used in intervention studies as a self-monitoring tool for the promotion of physical activity in children [28,29,30,31,32,33]. However, given that the accuracy of the Fitbit monitors for children was unknown, a caveat of these previous studies was that the researchers applied a research-grade monitor such as ActiGraph or a SenseWear armband to ensure a collection of accurate estimates of PA data [28]. However, using those research-grade activity monitors in addition to Fitbit monitors may have hindered achieving high adherence rates due to the increased burden of participants, especially in children.…”
Section: Discussionmentioning
confidence: 99%
“…Data from screening days (n = 175) and all days with a watch wear time < 50% between 6AM and 10PM were excluded from analyses regarding daytime measurements (146 study days), while all days with a watch wear time < 50% between 0AM and 5AM (268 study days) were excluded from analyses regarding nocturnal measurements. This 50% threshold has been chosen in earlier studies as well [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%